(untitled) (Research, Society and Development, 2022)
Equine piroplasmosis is a disease transmitted by ticks infected by the protozoa Babesia caballi known as Babesiosis or Teileriosis. Clinical manifestations range from fever, anemia, apathy, to acute conditions where the animal becomes a reservoir of this microorganism causing reproductive losses in mares. The aim of this study was to identify the DNA sequences of pathogens and diagnose equine piroplasmosis by conventional PCR technique. 2 mL of blood were collected from 50 equine females of the Brasileiro de Hipismo (HB), Undefined Breed (SRD) and Quarter Horse breeds, of different ages, belonging to stud farms in the Northeast region of Brazil. The animals were divided into 2 groups, 9 animals in the donor group and 41 animals in the recipient group. The blood was sent to the molecular biology laboratory to be used in the detection of Babesia spp. Of the 50 equine females tested, none were positive for the protozoan Babesia spp. Result of good sanitary management and control of ectoparasites in donor and recipient mares.